Assessing the Triple Deficit Hypothesis for Major South Asian Countries: A Panel Data Analysis - Shastri, Shruti; Giri, A.K.; Mohapatra, Geetilaxmi (International Journal of Economics and Financial Issues, 2017)
The paper examines the ‘triple deficit hypothesis'-an extension of the ‘twin deficit hypothesis' with inclusion of private saving gap for a panel of five South Asian countries, namely India, Pakistan, Bangladesh, Srilanka and Nepal for the period 1985-2015. The results based on first and second generation panel cointegration tests indicate long-run relationship among budget balance (BB), current account balance (CAB) and private saving gap. The long-run coefficients obtained using MG-DOLS, MG-FMOLS and CCEMG indicate positive impact of BB and private saving gap on CAB thus confirming triple deficit hypothesis. The causality analysis reveals feedback relationship between CAB and BB implying that improvement in CAB requires fiscal austerity but fiscal adjustment is not fully policy controlled and requires adjustment in current account. Further, the causation also runs from saving gap to CAB and BB implying that plugging the saving gap would help improve both current account and budget balance. Keywords: Triple Deficit Hypothesis, South Asia, Panel Cointegration, Panel Causality, GM-DOLS, GM- FMOLS, CCEMG Estimator JEL Classifications: E60, F32, H62